Development of an Augmented Reality (AR) Anatomy Application to Enhance Practical Skills in Vocational Health Education - Yoga Sahria (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2026)
Vocational health education, particularly diploma-level nursing programs, faces challenges in anatomy learning that still rely on conventional methods using mannequin models and two-dimensional atlases. This study aimed to develop and evaluate an Android-based Augmented Reality (AR) anatomy application designed for vocational nursing students at STIKES Al Islam Yogyakarta. The development process employed the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Usability evaluation was conducted using the User Experience Questionnaire (UEQ) and the System Usability Scale (SUS) involving 40 students. The UEQ results showed an overall score of 1.80 (Excellent category), with the Novelty scale achieving the highest score (1.93) and the Efficiency scale the lowest (1.68). The average SUS score was 81.3, categorized as Excellent/Grade A. Effectiveness testing using pre-test and post-test assessments demonstrated an improvement in practical examination scores from an average of 55.4 to 81.1, with an N-gain score of 0.57 (moderate category). The findings indicate that the AR anatomy application is feasible for use and effective in improving the practical skills of vocational nursing students.